MOTIVASI INTRINSIK DAN EKSTRINSIK DALAM PEMBELAJARAN BAHASA ARAB - Amirul Mukminin (LP2M Universitas Ibrahimy, 2016)
In the process of teaching and learning will definitely be an interaction between teachers and students, which teachers act as informants, mentor, motivator, facilitator, mediator, and evaluators. Motivator is the most important role of teachers in fostering the spirit of students to learn. In addition to the interaction with the teacher and the student, the learning process also there is interaction with the environment, and the environment also affects the emergence of a sense of fun in the learning process. MTs Salafiyah Syafi’iyah Sukorejo Situbondo and MTs SA Al-Hidayah Kota Batu – Malang are the two institutions that have a strong interaction among teachers, students, and the environment that cause students delighted in learning, especially in learning Arabic. Therefore, the researchers made these two institutions as a model of learning Arabic in junior level. In the present study, researcher intend to describe, examine and analyze student motivation in learning Arabic in junior Salafiyah Shafi'ites Sukorejo Situbondo and MTs SA Al-Hidayah Batu-Malang.